The Place Of War In Marxist Analyses Of Primitive Accumulation - Daniel Egan (World Review of Political Economy, 2022)
It has long been understood by Marxists, including Marx himself, that primitive accumulation was not limited to the historical origins of capitalism. Instead, extra-economic processes of capital accumulation continue to be relevant throughout the subsequent development of capitalism. An examination of the classic analyses of primitive accumulation made by Karl Marx and Rosa Luxemburg suggests that the most significant contemporary interpretation of the concept—David Harvey’s accumulation by dispossession—fails to properly account for the role played by war and military power in capital accumulation today. This is the product of both a problematic interpretation of Marx’s and Luxemburg’s analyses of primitive accumulation as well as a problematic interpretation of the 2003 US invasion of Iraq. I argue that Marx and Luxemburg continue to offer a more fruitful foundation from which to address this question.